Pengaruh Model Pembelajaran Demonstrasi dengan Bantuan Media Audiovisual terhadap Hasil Belajar Siswa Sekolah Dasar pada Pembelajaran Tematik - Eli Mufidah; Siti Zaitun (IBTIDA', 2021)
This study aims to describe the implementation of thematic learning using a demonstration model with the help of audiovisual media to improve learning outcomes of elementary school students. The subjects of this study were teachers and students of five grade . The research method used was quantitative case studies in accordance with the focus of the study. Data collection techniques used in this study were interviews, observation and written tests. Instruments for measuring learning outcomes using pre-test and post-test in the form of multiple choice questions. While the data analysis technique used hypothesis testing and to determine the increase in student learning outcomes using paired simple t-test. The results showed that based on the significance result of 0.00 <0.05, by looking at the results of the Paired Samples t-test table above, it is known that Ho is rejected and Ha is accepted, while the results of the Paired Samples Corelations table show a correlation number of "0.791> 0.05". So thus significantly the demonstration model with the help of audiovisual media has an effect on the learning outcomes of five grade students at MI Miftahul Ulum Kebalankulon.